Moving towards a core measures set for patient safety in perioperative care: An e-Delphi consensus study - Dinis-Teixeira, J.P. (2024)
A Core Measures Set (CMS) is an agreed standardized group of measures that should be assessed and reported in research for a specific condition or clinical area. This study undertook the development of a CMS for Patient Safety through a two-round, web-based Delphi consensus approach, in the context of the "Improving quality and patient SAFEty in surgical care through STandardisation and harmonization of perioperative care in Europe" (SAFEST) project-a collaborative, patient-centered and evidence-based European Union-funded project that aims to generate action-oriented evidence in perioperative care. We developed an Initial List of Measures via an umbrella review following the deployment of an e-Delphi method with an inclusive panel of experts to prioritize measures towards a consensualized Final List of Measures. All measures were rigorously assessed for both importance and feasibility. After the two rounds of the e-Delphi consensus method we observed 13 preoperative measures (40.6% of the initial number), 24 intraoperative measures (66.7%), 25 postoperative measures (20.3%) and 23 mixed period measures (41.1%) met consensus criteria for both importance and feasibility. Higher scores were detected in importance ratings compared to feasibility across all groups of measures. Importantly, numeric averages regarding pain-related measures differed in the assessment of patients when compared to that of Healthcare Professionals (HCPs). This work not only informs future SAFEST iterations but also sets a precedent for research into valid, patient-centered, and action-oriented perioperative safety measures.